Improvement of Diet Behavior in Clients with Diabetes Mellitus Through Health Education - Siti Utami Dewi; Deinera Rachel Furtunah F. D (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2020)
Diabetes mellitus (DM) is a disease that is a problem in public health. DM is a metabolic disorder characterized by hyperglycemia (an increase in serum glucose levels) due to lack of the hormone insulin, decreased effect of insulin and or both. Diet or diet is an important determinant that determines obesity and insulin resistance, so the provision of health education is a way to maintain the stability of insulin in DM clients. This case study aims to get an overview of the implementation of health education in improving the eating habits of DM clients. The method used is descriptive in the form of case studies with the criteria that the subject is a family with diabetes mellitus health problems through health education intervention about diet. The results of the case study showed that there was a decrease in blood sugar levels, good motivation of the families in implementing the DM diet, and behavioral changes by 76% (good category) in subject I, as far as subject II behavior change was 80% (good category ) Based on the results of this case study it is expected that nurses through health cadres are able to monitor the implementation of DM diet in families with optimal DM health problems.